Improving adenoviral vectors and strategies for prostate cancer gene therapy - Tamura, Rodrigo Esaki; Luna, Igor Vieira de; Lana, Marlous Gomes; Strauss, Bryan E. (Clinics, 2019)
Gene therapy has been evaluated for the treatment of prostate cancer and includes the application of adenoviral vectors encoding a suicide gene or oncolytic adenoviruses that may be armed with a functional transgene. In parallel, versions of adenoviral vector expressing the p53 gene (Ad-p53) have been tested as treatments for head and neck squamous cell carcinoma and non-small cell lung cancer. Although Ad-p53 gene therapy has yielded some interesting results when applied to prostate cancer, it has not been widely explored, perhaps due to current limitations of the approach. To achieve better functionality, improvements in the gene transfer system and the therapeutic regimen may be required. We have developed adenoviral vectors whose transgene expression is controlled by a p53-responsive promoter, which creates a positive feedback mechanism when used to drive the expression of p53. Together with improvements that permit efficient transduction, this new approach was more effective than the use of traditional versions of Ad-p53 in killing prostate cancer cell lines and inhibiting tumor progression. Even so, gene therapy is not expected to replace traditional chemotherapy but should complement the standard of care. In fact, chemotherapy has been shown to assist in viral transduction and transgene expression. The cooperation between gene therapy and chemotherapy is expected to effectively kill tumor cells while permitting the use of reduced chemotherapy drug concentrations and, thus, lowering side effects. Therefore, the combination of gene therapy and chemotherapy may prove essential for the success of both approaches.